TAXONOMY OF TYPES OF TEACHER'S PROFESSIONAL REFLECTION: INTERDISCIPLINARY CONTEXT - V. Zhelanova (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article presents the importance of professional reflection as an important teacher's professional skill according to the position that reflexive processes virtually permeate teacher's professional activity which requires high level of reflection of self-knowledge and responsibility for another person. It is found that future teacher's professional reflection is the synthesis of reflective thinking, reflective activities and reflective consciousness aimed at self-analysis, self-awareness, self-perception, own and common activities and perception in "the eyes of others" according to the context of future professional activities throughout its various aspects. It is proved that the following taxonomy of types of teacher's professional reflection which includes their classification according to their implementation, to the aspects of educational activities, to the focus, time orientation and teacher's functional positions, is an interdisciplinary synthesis of philosophical and psychological interpretation of the implementation fields of reflection (activity, thinking, self-awareness, self-regulation, communication and cooperation), its functions, the essence of reflection as the unique person's quality (reflexivity), the state of awareness of anything (reflection), the process of representation of own content in person's mind (reflection). 14 Педагогічна освіта: теорія і практика. Психологія. Педагогіка Based on the idea of activity-oriented approach to the study of this phenomenon, the author substantiates the approaches to the understanding of the concept of "professional reflection", in particular, aspect-activity approach to educational reflection. From this perspective, it is defined teacher's professional reflection as an activity aimed at analysis and awareness of their personal qualities, at understanding how it is perceived by the other people; on self-regulation and adjustment of own activity and student's personality, as well as the development of educational technology of future professional career. The author notes the diversity of the phenomenon of pedagogical reflection, which is reflected in its numerous typologies: personal, interpersonal, object-functional, and methodological types of pedagogical reflection. It is emphasized that taking into account the complexity, multidimensionality and dynamism of the considered phenomenon, it is undoubtedly necessary its further scientific exploration in the format of acmeology to determine the acme- route of development of teacher's professional reflection as the whole as well as its separate types.